P26 CT abdomen and pelvis for unprovoked pulmonary embolism – what is the best practice?. (15th November 2016) - Wahida, R; Ahmad, S; Saunders, B; How, N; Anwar, M
Abstract : Background: NICE guidelines advocate further investigations for cancer with an abdomino-pelvic CT scan (CT A/P) in all patients aged over 40 years with a first unprovoked deep vein thrombosis (DVT) or pulmonary embolism (PE) who do not have signs or symptoms of cancer based on initial investigation. 1 Recent prospective study showed no difference between 'limited' screening and CT A/P in diagnosing occult cancer. 2 We aimed to establish whether the number of new malignancies detected justified the risk of radiation exposure from performing a CT A/P in patient with unprovoked PE. Methods: We performed a retrospective analysis of all CT Pulmonary Angiograms (CTPA) performed during a one year period (2014–2015) in a district general hospital. Records of those patients with confirmed pulmonary embolism on CTPA (n = 254) were examined to ascertain whether performing CT A/P increased the detection rate of occult malignancy. Results: 124 (49%) out of a total 254 patients had an acute unprovoked PE. Of these, 6 patients were under the age of 40 years. Out of the remaining 118 patients, 80 (68%) patients underwent CT A/P. Unexpected malignancy was found in 3 (4%) of these 80 patients. No evidence of malignancy has been found in those patients that did not undergo CT A/P (n = 38) so far based on the follow up clinical encounters – both as an in-patient and outpatient. Conclusion: Our data support the finding that the routine use of CT A/P in patients with unprovoked PE doesn't detect significant number of occult malignancies. References: Singh B, et al . National institute for health and care excellence . Venous thromboembolic diseases: diagnosis, management and thrombophilia testing. Nov 2012. Carrier M, et al . Screening for occult cancer in unprovoked venous thromboembolism. NEJM 2015;373 :8.